Emotions and Reflexivity in Health & Social Care Field Research (Springer International Publishing, 2018)
This book is about emotions and reflexivity when doing field research in health and social care settings. Health and social care students often undertake field research in their own area of practice using observation and interviews. Chapters draw on research carried out in a number of fields including HIV related infertility and adoption, primary care in Africa, cancer and palliative care, infertility and excluded young people to explore issues relevant to emotions and reflexivity from the perspective of the researcher and research participants. All contributing authors have a dual identity as researchers and health or social care professionals. The book was born of the two editors, who are experienced research supervisors, observing that many PhD students struggle to manage the emotions elicited in the field when researching. They identify three main causes - health and social care deals with painful topics; observation and interviews bring student into contact with powerful feelings which need processing; there is very little advice and discussion of how a PhD student manages emotions in the field and students therefore frequently struggle on their own. This insightful volume will be of great interest to scholars and students in all areas of academic study, but particularly to those who chose to study health and social care whether they are professionals or not.